Integration of carbon-doped ZnO/S cathode and silicon/graphene nanoplate anode for silicon-sulfur batteries - Aslfattahi, Navid; Kiai, Maryam Sadat; Baydogan, Nilgun; Samylingam, Lingenthiran; Kadirgama, Kumaran; Kok, Chee Kuang
The advancement of modified anodes and cathodes for the next generation of sulfur-based batteries has become a prominent focus of research. This study introduces a methodology for the design and synthesis of silicon/graphene nanoplates (Si/GNPs) through a one-step hydrothermal process. Additionally, we suggest nanocomposite carbon-doped ZnO/S as a potential cathode material through the urea-assisted thermal decomposition of zinc acetate. C/ZnO/S has the special capability to alleviate volume change and hinder sulfur dissolution of the electrolyte. Additionally, ZnO possesses a superior distribution of sulfur in the ZnO/S composite and enhanced sulfur conversion reactions. This configuration of the cell is mentioned for the first time and shows an outstanding retention capacity of 916 mAh g–1 after 500 cycles, indicating a minimal decay rate of merely 0.047% per cycle.